ANALISIS PERBANDINGAN PENGGUNAAN ANTENA OMNIDIRECTIONAL DAN MIKROSTRIP PADA RECEIVER SISTEM CERDAS MONITORING PASIEN - Azzam Rasyiq El-Faraby; Ponco Siwindarto; Muhammad Fauzan Edy Purnomo (Jurnal Mahasiswa TEUB, 2023)
In implementing an IoT-based patient monitoring system, an antenna is needed that is designed to strengthen signal reception. The designed IoT system is a communication of 2 microcontrollers that can transmit important parameters of the patient's condition. The design of the microstrip antenna is integrated into the receiving side of the LoRa 32 V2 SX1276 microcontroller. Thedesign of a microstrip antenna begins with designing and optimizing using the CST 2018 software. The parameters that are the main points are gain, return loss, and axial ratio. Microstrip antenna specifications use an FR-4 substrate with a thickness of 1.6 mm. In addition, this antenna is designed at a frequency of 920-925 MHz, according to the working frequency of the LoRa 32 V2SX1276 microcontroller. Keywords : Antenna, microstrip, lora, CST 2018